Dynamic effects of single fiber break in unidirectional glass fiber-reinforced composites. (April 2017) - Ganesh, Raja; Sockalingam, Subramani; (Gama) Haque, Bazle Z; Gillespie, John W
In a unidirectional composite under static tensile loading, breaking of a fiber is shown to be a locally dynamic process that leads to stress concentrations in the interface, matrix and neighboring fibers that can propagate at high speed over long distances. To gain better understanding of this event, a fiber-level finite element model of a two-dimensional array of S2-glass fibers embedded in an elastic epoxy matrix with interfacial cohesive traction law is developed. The brittle fiber fracture results in release of stored strain energy as a compressive stress wave that propagates along the length of the broken fiber at speeds approaching the axial wave-speed in the fiber (6 km/s). This wave induces an axial tensile wave with a dynamic tensile stress concentration in adjacent fibers that diminishes with distance. Moreover, dynamic interfacial failure is predicted where debonding initiates, propagates and arrests at longer distances than predicted by models that assume quasi-static fiber breakage. In the case of higher strength fibers breaks, unstable debond growth is predicted. A stability criterion to define the threshold fiber break strength is derived based on an energy balance between the release of fiber elastic energy and energy absorption associated with interfacial debonding. A contour map of peak dynamic stress concentrations is generated at various break stresses to quantify the zone-of-influence of dynamic failure. The dynamic results are shown to envelop a much larger volume of the microstructure than the quasi-static results. The implications of dynamic fiber fracture on damage evolution in the composite are discussed.